Effect of chronic undernutrition on body mass and mechanical bone quality under normoxic and altitude hypoxic conditions. Issue 9 (10th March 2016) - Lezon, Christian; Bozzini, Clarisa; Agûero Romero, Alan; Pinto, Patricia; Champin, Graciela; Alippi, Rosa M.; Boyer, Patricia; Bozzini, Carlos E.
Abstract: Both undernutrition and hypoxia exert a negative influence on both growth pattern and bone mechanical properties in developing rats. The present study explored the effects of chronic food restriction on both variables in growing rats exposed to simulated high-altitude hypoxia. Male rats ( n 80) aged 28 d were divided into normoxic (Nx) and hypoxic (Hx) groups. Hx rats were exposed to hypobaric air (380 mmHg) in decompression chambers. At T0, Nx and Hx rats were subdivided into four equal subgroups: normoxic control and hypoxic controls, and normoxic growth-restricted and hypoxic growth-restricted received 80 % of the amount of food consumed freely by their respective controls for a 4-week period. Half of these animals were studied at the end of this period (T4 ). The remaining rats in each group continued under the same environmental conditions, but food was offered ad libitum to explore the type of catch-up growth during 8 weeks. Structural bone properties (strength and stiffness) were evaluated in the right femur midshaft by the mechanical three-point bending test; geometric properties (length, cross-sectional area, cortical mass, bending cross-sectional moment of inertia) and intrinsic properties of the bone tissue (elastic modulus) were measured or derived from appropriate equations. Bone mineralisation was assessed by ash measurement of the left femur. These data indicate that the growth-retarded effects of diminished food intake, induced either by food restriction or hypoxia-related inhibition of appetite, generated the formation of corresponding smaller bones in which subnormal structural and geometric properties were observed. However, they seemed to be appropriate to the body mass of the animals and suggest, therefore, that the bones were not osteopenic. When food restriction was imposed in Hx rats, the combined effects of both variables were additive, inducing a further reduction of bone mass and bone load-carrying capacity. In all cases, the mechanical properties of the mineralised tissue were unaffected. This and the capacity of the treated bones to undergone complete catch-up growth with full restoration of the biomechanical properties suggest that undernutrition, under either Nx or Hx conditions, does not affect bone behaviour because it remains appropriate to its mechanical functions.